Artemin has potent neurotrophic actions on injured C-fibres. - Bennett, D; Boucher, T; Michael, G; Popat, R; Malcangio, M; Averill, SA; Poulsen, K; Priestley, J; Shelton, D; McMahon, S (2006)
In this study, we have investigated the effects of artemin (ARTN), one of the glial cell line-derived neurotrophic factor (GDNF) family of neurotrophic factors, on C-fibres following nerve injury in the adult rat. GDNF family receptor alpha (GFRalpha) 3, the ligand binding domain of the ARTN receptor, is expressed in 34% of dorsal root ganglion (DRG) cells, predominantly in the peptidergic population of C-fibres and in a proportion of the isolectin B4 (IB4)-binding population. Interestingly, only 30% of GFRalpha3-expressing DRG cells co-expressed RET (the signal transducing domain). In agreement with previous studies, treatment with ARTN prevented many of the nerve injury-induced changes in the histochemistry of both the peptidergic and the IB4-binding populations of small, but not large, diameter DRG cells. In addition, ARTN treatment maintained C-fibre conduction velocity, and C-fibre evoked substance P release within the dorsal horn following nerve injury. ARTN was also protective following capsaicin treatment, which produces selective C-fibre injury. Given the potent neurotrophic actions of ARTN on C-fibres, it may therefore provide potential for the treatment of nerve injury, particularly in the maintenance of small fibre function.